HUBUNGAN JENIS PERMAINAN TERHADAP PERILAKU SOSIAL ANAK DI TAMAN KANAK-KANAK KEC. TELANAIPURA JAMBI - Gusti Lestari Handayani (Poltekkes Kemenkes Jambi, 2016)
Growth of globalization era and technology influence many matter, including type game of child,representing one of the factor influencing growth of child. Social child maturity of pre school representchild 3-6 year in have interaction with good vinicity environment or others verbal and also nonverbal inorder to fulfilling its requirement to be able to be accepted by friend coeval and adult expecting him toobtain;get to feel to be required and feel to worth. Problems of early age wasnot finished from since earlycan cause problems of growth next period, its influence not even pertinent but environment. Recentlyproblems of social that happened was improvement. Early study researcher, skill of social exist in one ofnursery School in Jambi seen that child social maturity still lower ex: do not want to be in rotation useplaything, weeping when clashing with friend and also predominating class even have the character ofagresifitas.Target of this research is to know influence type of game to preschool social behavior in NurserySchool Kec. Telanaipura Jambi.Design reseach was crossectional study, minimum sampel 138 child with α = 0,05 and β = 5%.Location of study in Nursery School Kec. Telanaipura Jambi that Is TK Al Aqsa, TK Builder and of TKAdhyaksa. Time of research in Juni-Juli 2012. Data collected through observation and kuisioner. Dataanalysis using statistical test: Chi-Square.Result:type of game have significan relationship to preschool social behavior with value p 0,005.So that require to be improved attention to give of plaything child able to improve ability of social behaviorwhich are positive.